Water Demand Analysis of Sugarcane Based on Crop Simulation Model (Case Study: Kediri Regency, East Java) (Agromet, 2019)
Sugarcane productivity is naturally affected by climate variables and limited by the water availability. This study simulated a water balance model to estimate sugarcane water requirement and to estimate the best planting time as well based on its optimum productivity in Kediri Regency. Water requirement was estimated by water loss of evapotranspiration following FAO No. 24, while the productivity was based on mid-maturing sugarcane growth and development. Sugarcane rainfed area in Kediri Regency needs approximately 26-128 mm water per month based on its loss by evapotranspiration. The value varied due to the growth phase. More than 60% water was used in vegetative phase for developing buds and stem elongation of about 3-9 months after planting. The highest sugarcane productivity was obtained in July-September as the best planting time shown by simulation. Moreover, water deficiency during mid-season of sugarcane growth could decrease productivity by a significant amount. The work presented here could be used as a tool to help decision makers for irrigation management and select the best planting date.